Balancing Act: Examining the Relationship Between Role Conflict and Marital Satisfaction in Dual-Earner Families - Nugrahani, Andita; Maryana; Izura Rochma (Sahabat Publikasi Kuu, 2024)
Background: This study aims to investigate the correlation between dual role conflict and marital satisfaction in married women with dual-earner family scheme in Batam, Method: The design is a correlational analysis which employs quantitative approach. The sample of the study was married women with dual-earner family scheme in Batam who met the qualification criteria. The data collecting technique employs purposive sampling with 151 respondents in total. The data collecting means employs a standardized form of questionnaire in which Work Family Conflict Scale used to assess dual role conflict levels, and ENRICH Marital Satisfaction Scale to assess marital satisfaction levels. Results: Out of 151 respondents, 68.9% indicated dual role conflict at moderate levels, and 88.7% indicated marital satisfaction at moderate levels. From the bivariate analysis using Pearson correlation, the significance value is 0.003<0.05, with coefficient value -0.237. Therefore, dual role conflict and marital satisfaction have significantly a negative correlation. Conclusion: With correlational coefficient value -0.237, the correlation between dual role conflict and marital satisfaction is significantly negative. This means the lower the levels of dual role conflict, the higher the levels of marital satisfaction in married women with dual earner family scheme.